Dilema Peran Ganda: Studi Fenomenologis Perempuan Buruh di Kabupaten Pinrang - Sadriani, Andi (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to deeply understand the experiences of female workers in Pinrang Regency in carrying out their dual roles as breadwinners and housekeepers. This study uses a qualitative approach with a phenomenological method to explore the subjective meaning of participants' life experiences. Data were collected through in-depth interviews with a number of female workers and analyzed using thematic analysis techniques. The results of the study show five main themes that represent the dynamics of the dual roles of female workers, namely: (1) economic motivation as the main driver of work, (2) difficulty in dividing time between work and household chores, (3) psychological and physical stress due to dual workloads, (4) adaptive strategies in navigating roles, and (5) views on social support and policies that are still minimal and less supportive of women's needs. This study confirms that female workers are in a vulnerable position due to the patriarchal social structure that has not fully changed. These findings provide an important contribution to efforts to strengthen the voices of female workers and encourage the formulation of fairer and gender-responsive public policies, especially in the informal labor sector in rural areas.